Women in leadership: an analysis of the gender pay gap in ASX‐listed firms. (23rd November 2015) - Hutchinson, Marion; Mack, Janet; Verhoeven, Peter
Abstract: This study provides evidence that after several decades of fighting for equal pay for equal work, an unexplained gender pay gap remains amongst senior executives in ASX‐listed firms. After controlling for a large suite of personal, occupational and firm observables, we find female senior executives receive, on average, 22.58 percent less in base salary for the period 2002–2013. When executives are awarded performance‐based pay, females receive on average 16.47 percent less in cash bonus and 18.21 percent less in long‐term incentives than males. The results are robust to using firm fixed effects and propensity‐score matching. Blinder–Oaxaca decomposition results show that the mean pay gap cannot be attributed to gender differences in attributes, including job titles. Instead, the results point to differences in returns on firm‐specific variables, in particular firm risk.